Phospho-Profiling Linking Biology and Clinics in Pediatric Acute Myeloid Leukemia - Angela Schumich; Michaela Prchal-Murphy; Margarita Maurer-Granofszky; Andrea Hoelbl-Kovacic; Nora Mühlegger; Ulrike Pötschger; Sabine Fajmann; Oskar A. Haas; Karin Nebral; Nils von Neuhoff; Martin Zimmermann; Heidrun Boztug; et al. (HemaSphere, 2020)
Abstract. Aberrant activation of key signaling-molecules is a hallmark of acute myeloid leukemia (AML) and may have prognostic and therapeutic implications. AML summarizes several disease entities with a variety of genetic subtypes. A comprehensive model spanning from signal activation patterns in major genetic subtypes of pediatric AML (pedAML) to outcome prediction and pre-clinical response to signaling inhibitors has not yet been provided. We established a high-throughput flow-cytometry based method to assess activation of hallmark phospho-proteins (phospho-flow) in 166 bone-marrow derived pedAML samples under basal and cytokine stimulated conditions. We correlated levels of activated phospho-proteins at diagnosis with relapse incidence in intermediate (IR) and high risk (HR) subtypes. In parallel, we screened a set of signaling inhibitors for their efficacy against primary AML blasts in a flow-cytometry based ex vivo cytotoxicity assay and validated the results in a murine xenograft model. Certain phospho-signal patterns differ between genetic subtypes of pedAML. Some are consistently seen through all AML subtypes such as pSTAT5. In IR/HR subtypes high levels of GM-CSF stimulated pSTAT5 and low levels of unstimulated pJNK correlated with increased relapse risk overall. Combination of GM-CSF/pSTAT5high and basal/pJNKlow separated three risk groups among IR/HR subtypes. Out of 10 tested signaling inhibitors, midostaurin most effectively affected AML blasts and simultaneously blocked phosphorylation of multiple proteins, including STAT5. In a mouse xenograft model of KMT2A-rearranged pedAML, midostaurin significantly prolonged disease latency. Our study demonstrates the applicability of phospho-flow for relapse-risk assessment in pedAML, whereas functional phenotype-driven ex vivo testing of signaling inhibitors may allow individualized therapy.